THE USE OF MISTAKE BUSTER TECHNIQUE TO IMPROVE THE STUDENTS’ WRITING SKILL - Bahrun Amin (Universitas Muhammadiyah Makassar, 2015)
This research aimed to find out whether or not Mistake Buster Technique is effective to be used in writing a recount composition and find out the extent to which Mistake Buster Technique improve the ability of students in writing a recount composition for the Second Grade Students. A quasi-experimental design was employed with two classes of the second graders at one school in Makassar selected purposively as a sample. The data were obtained through a pre-test and a post-test. The writing assessment was adopted from Depdikbud (1996) covering language use and organization. The findings were analyzed statistically sing independent t-test procedure.The research findings indicated that the use of Mistake Buster Technique could improve the students‘ writing skill in language use and organization in writing recount composition. It was proved by the students’ mean score of experimental class in pre-test was (10.125) and in post-test was (65.5).While the mean score of control class in pre-test was (9.375) and in post-test was (41.125). The findings of this research shows that the value of t-test in the posttest is higher than t table (4.28 2,02). It means that there was a significant difference of the students’ writing skill in language use and organization in writing recount composition before and after being taught using Mistake Buster Technique at the Second Grade of SMPN 33 Makassar. The statistical computation showed that Mistake Buster Technique was likely effective in improving the students’ writing skill on language use and organization in writing recount composition.